2015
DOI: 10.2196/jmir.3975
|View full text |Cite|
|
Sign up to set email alerts
|

Comparative and Cost Effectiveness of Telemedicine Versus Telephone Counseling for Smoking Cessation

Abstract: BackgroundIn rural America, cigarette smoking is prevalent and health care providers lack the time and resources to help smokers quit. Telephone quitlines are important avenues for cessation services in rural areas, but they are poorly integrated with local health care resources.ObjectiveThe intent of the study was to assess the comparative effectiveness and cost effectiveness of two models for delivering expert tobacco treatment at a distance: telemedicine counseling that was integrated into smokers’ primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
133
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(145 citation statements)
references
References 28 publications
9
133
2
1
Order By: Relevance
“…In the smoking cessation research literature, this is particularly evident in efforts to develop and evaluate technology-based interventions, including telemedicine (Richter et al, 2015), web-based (Shahab & McEwen, 2009) and text messaging-based (Kong, Ells, Camenga, & Krishnan-Sarin, 2014) programs. This is a relatively nascent but fast growing, area of research that often involves assessing the acceptability of interventions that differ in the frequency or intensity of technology-related aspects of treatment.…”
Section: Introductionmentioning
confidence: 99%
“…In the smoking cessation research literature, this is particularly evident in efforts to develop and evaluate technology-based interventions, including telemedicine (Richter et al, 2015), web-based (Shahab & McEwen, 2009) and text messaging-based (Kong, Ells, Camenga, & Krishnan-Sarin, 2014) programs. This is a relatively nascent but fast growing, area of research that often involves assessing the acceptability of interventions that differ in the frequency or intensity of technology-related aspects of treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Only three studies of a videoconferencing smoking cessation intervention were identified, but none of these studies included WLHIV. [32][33][34] Two studies were conducted in the USA: one on Korean American women and the other one on general smokers in primary care clinics. 32,33 Both studies found no differences in videoconferencing and telephone counseling cessation interventions.…”
Section: Kim Et Almentioning
confidence: 99%
“…[32][33][34] Two studies were conducted in the USA: one on Korean American women and the other one on general smokers in primary care clinics. 32,33 Both studies found no differences in videoconferencing and telephone counseling cessation interventions. In the study with Korean American women, however, cotinine-confirmed abstinence rate was 10% higher among Korean women who received a videoconferencing intervention than among those who received a telephone counseling intervention (40% vs. 30%).…”
Section: Kim Et Almentioning
confidence: 99%
“…Such studies are almost non-existent, although studies comparing the impact of other platforms on health behavior do exist, such as telemedicine versus telephone counseling (Richter et al 2015) or web-based versus paper-based (Ali et al 2014).…”
Section: Implications For Further Researchmentioning
confidence: 99%